PERHAPS HERETICAL - Alessandra Bonazzi (Bollettino della Società Geografica Italiana)
This is a brief reply to Matteo Marconi’s article. I have been challenged along with Marcello Tanca with the criticism of practicing a geography that is eccentric but unaware of the logical continuity between modernity and postmodernity. The suspicion is that the subversive impact of the “culturalist” turning point is in fact compromised by a system of production of truth akin by logic, operation and subject to that of the modern era. I have therefore attempted to formulate a possible answer to these comments and to the critical insights of Matteo Marconi, whom I thank for having requested a response to his writing.